Қарақалпақстан Республикасы қазақ сөйлесиминде ушырасатуғын АРАБ-ИРАН ТИЛЛЕРИНЕН кирген СӨЗЛЕР ҳаққында - Қуттымуратова, Ы.А. (FAN va JAMIYAT, 2020)
The author of the article describes the language peculiarities of Kazakhs living in Kungrad district of Karakalpak Republic. On the base of gathered materials in the region it was analyzed some lexical peculiarities of Kazakhs comparing with other Turkic languages (Karakalpak, Uzbek and Turkmenian). The authors focus their attention on linguistic relations of accents. The article deals with elements borrowed from the Arabic-Iranian language in this dialect.